Donor coordination: a basic requirement for more efficient and effective development cooperation - Guido Ashoff (Deutsches Institut für Entwicklungspolitik (DIE), 2004)
The international community of official development aid donors currently comprises 37 countries (bilateral donors) and some 30 international organizations (multilateral donors). This multiplicity of donors, many with projects, programmes, interests, concepts, structures and procedures of their own, increases the transaction costs of development cooperation for donors and partner countries and diminishes the possible impact of development cooperation. Donor coordination is meant to counteract this and has become an important item on the international development agenda.The underlying reason for this is the growing pressure to improve the efficiency and effectiveness of development cooperation exerted, on the one hand, by the ambitious Millennium Development Goals (MDGs) and the comprehensive poverty reduction strategies being pursued by many low-income countries and, on the other hand, by scarce development cooperation resources. At the International Conference on Financing for Development held in Monterrey in 2002, the donors and partner countries committed themselves to closer coordination. The OECD's Development Assistance Committee (DAC) drew up detailed recommendations, which were endorsed by many donors and developing countries in February 2003 ( Rome Declaration on Harmonisation ). A number of donors subsequently put forward action plans (Germany doing so in April 2003). Their implementation will be considered at an international conference to be held in Paris in early March 2005.Although significant progress has been made, donor coordination is still a challenge. The frame of reference is to be formed by the strategies established by the partner countries on their own responsibility, with which the donors are to align their contributions. Donor coordination is ideally undertaken by the partners, but they must be willing and able to do so. For the donors this means taking seriously and neither overtaxing nor undermining their partner countries' ownership and capacity with respect to their development. The donors must also be willing to subordinate their individual interests, concepts and visibility to a joint approach appropriate to development.
Keywords: 330